A CONCEPT OF UNIVERSAL QUANTUM JUMP - Khoder, Mazen (Matematichki Bilten, 2020)
It is known that quantum mechanics is one of the most successful theories in physics across the entire history of physics. Nevertheless, many believe that its foundations are still not really understood like: wave-particle duality, interference, entanglement, quantum tunneling, uncertainty principle, wave collapse, vacuum energy, relation between classical mechanics and quantum mechanics, classical limit, quantum chaos, etc., and the continuous failures in the unifying between relativity theory and quantum theory may be an indication about a problem in the foundations. This paper aims at discovering the first small step in the path of solving and understanding these quantum puzzles, in fact, the key to solving quantum puzzles is by understanding the reality of the motion and how it occurs. This paper proposes a model of motion that generalizes the concept of "quantum jump". Actually, we have been able to deduce the principles of quantum mechanics so that the oddity of the quantum puzzles becomes easier to understand and interpret. And as a direct verification of this model of motion this paper deduces the Lamb shift effect without the need of introducing of the concept of vacuum energy fluctuations, and it also discusses that the universal basic law of motion must be broader than both quantum mechanics and classical mechanics.